Total pain and comfort theory: implications in the care to patients in oncology palliative care - Maria Cristina Freitas de Castro; Patrícia dos Santos Claro Fuly; Mauro Leonardo Salvador Caldeira dos Santos; Marléa Crescêncio Chagas (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To reflect on the possible connections between Katharine Kolcaba's Theory of Comfort and Cicely Saunders's concept of Total Pain and the implications to the care of the oncology palliative care patient. Method: Theoretical reflection based on a literature review carried out in May 2020, in the PubMed and LILACS databases, which sought to answer the question: "Are there any theoretical-conceptual connections between Kolcaba's Theory of Comfort and the concept of Total Pain by Saunders?" Results: The knowledge of the concepts presented allows redirecting the focus of care towards individualized actions to strengthen the patient and his participation in the choices of comfort interventions. Conclusion: Understanding the connections between the concept and theory presented provides the patient in oncology palliative care with individualized and qualified care, focused on the person and not on the disease and can contribute to a greater effectiveness of nursing interventions aimed at the relief of suffering.